"Tô na campanha": uma análise de uma proposta de popularização do teatro e da dança em Belo Horizonte (1998 2012) - Nádia Bueno Rezende (2013)
This research aimed to discuss a strategy to popularize theater and dance in Belo Horizonte, and to find out what the role and the representativeness of the Campaign for the Popularization of Theatre and Dance (CPTD) are in the political, cultural and artistic scenes of Minas Gerais from the point of view of its organizers. The study was conducted narrowing historiographically the presenttime, bounded by temporality from 1998 to 2012. The sources were gathered at both the collection library and the website of the Producers Guild of Performing Arts of Minas Gerais (MG-Sinparc): they are the General Reports of the CPTD editions, produced by the institution itself, which include newspaper clippings and documents containing reference to the numbers raised in each edition. Starting an axis that considers the production, distribution and consumption of art, the first chapter of this dissertation deals with the centrality of the deeds of CPTD in distribution, emphasizing the establishment of relations with the population between their advertising strategies. Everything is organized aiming integration around a common meaning, which was only possible through the mediation carried out by mass culture, obscuring differences and unifying tastes. However, this unification did not happen bypure action of hegemony. Mass culture has only become a mediator in the process of reconciliation between the classes because it was formed from the popular. Thesecond chapter made an effort to understand what art is for CPTD, reaching a discussion of the functions assigned to art in mass society. What can be shown from the sources listed are the tensions and conflicts involving the diversity of programming, regarding the establishment of criteria of artistic quality. Among the purely commercial art and the art that elevates the artist to the status of sole owner of knowledgeconsolidated by the aesthetics of fine art, mass culture promotes a third possibility: the dialectic art as the translation of its own production, distribution and consumption. Looking at it this way, in addition to organizing the art in commercial terms, the cultural industry also imposes to artists the public will. That's where the popular finds room in the mass: guided by a sense / sensory which translates a way to feel in mass and that found in photography, film and CPTD the expression of this new sensibility.